Clinical utility of intravitreal fluocinolone acetonide (Iluvien®) implant in the management of patients with chronic diabetic macular edema: a review of the current literature - Saedon H (Dove Medical Press, 2017)
Habiba Saedon,1 Astha Anand,1 Yit C Yang1,2 1Department of Ophthalmology, Royal Wolverhampton NHS Trust, Wolverhampton, West Midlands, 2School of Life and Health Sciences, Aston University, Birmingham, UK Abstract: The first-line therapy for patients with center-involving diabetic macular edema (DME) is with intravitreal anti-vascular endothelial growth factor (VEGF) agents, with or without adjunctive macular laser treatment. However, a significant proportion of patients have persistent and recurrent edema despite repeated anti-VEGF injections. The fluocinolone acetonide (FA) 190 µg intravitreal implant has been shown in pivotal clinical trials to be efficacious for the treatment of DME and has been approved in many countries for use in patients who have not responded to first-line therapy. In this report, we have collated the latest data from the increasing number of studies to illustrate the pattern of usage of the Iluvien FA implant for DME during the current anti-VEGF era. We have shown that there is now a wealth of published evidence from real-world studies to support the clinical utility of the FA implant in achieving further resolution of edema and improving visual acuity outcomes in this challenging group of patients. Keywords: fluocinolone acetonide, Iluvien, diabetic macular edema